1989
DOI: 10.1111/j.1365-2311.1989.tb00755.x
|View full text |Cite
|
Sign up to set email alerts
|

The photoperiodic responses and phenology of an English strain of the pea aphid Acyrthosiphon pisum

Abstract: 1. The response curves for the photoperiodic induction of the sexual forms (oviparae and males) differ significantly in an English clone of the pea aphid Acyrthosiphon pisum Hams. Male production is sharply peaked. The late summer scotophases (dark periods) that initiate male production are 1.0-1.5 h shorter than those that initiate ovipara production; the induction of males, but not oviparae, virtually ceases at scotophases longer than 12 h. This disparity suggests that there are two photoperiodic clocks.2. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 20 publications
5
43
0
Order By: Relevance
“…The age-dependent progeny patterns of apterae described in the present study are consistent with other reports (Kenten, 1955;Lamb & Pointing, 1975;Sharma et al, 1975;MacKay, 1987;Lees, 1989) and were previously discussed in detail by the author (Erlykova, 1997(Erlykova, , 1999. However, it must be noted that the tendency in this study for both apterae and alatae to produce initial and final batches of viviparae contrasts with the findings of MacKay et al (1983) and Vaz Nunes & Hardie (1996) who found no viviparae production at the end of progeny sequences of alatae.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The age-dependent progeny patterns of apterae described in the present study are consistent with other reports (Kenten, 1955;Lamb & Pointing, 1975;Sharma et al, 1975;MacKay, 1987;Lees, 1989) and were previously discussed in detail by the author (Erlykova, 1997(Erlykova, , 1999. However, it must be noted that the tendency in this study for both apterae and alatae to produce initial and final batches of viviparae contrasts with the findings of MacKay et al (1983) and Vaz Nunes & Hardie (1996) who found no viviparae production at the end of progeny sequences of alatae.…”
Section: Discussionsupporting
confidence: 82%
“…The simultaneous analysis of several aphid clones sometimes revealed the existence of local interclonal variability in the photoperi odic response (Blackman, 1971;Eisenbach & Mittler, 1987;Takada, 1988;MacKay, 1989;Smith & MacKay, 1989aMittler & Wilhoit, 1990;Mittler & Gorder, 1991;Lamb & MacKay, 1997;Dedryver et al, 1998), but usually only a few photoperiods were used. The photope riodic response curves for male and ovipara production in the pea aphid Acyrthosiphon pisum (Harris) over the com plete range of photoperiods is known for one clone from Cambridge (Lees, 1989). The object of the present work was to estimate the interclonal variability in the photope riodic response of the green form of the pea aphid from the Leningrad Province, the northernmost population studied to date, and to determine the intraclonal differ ences in the responses shown by apterae and alatae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, there may well be a temporal separation between the sexual forms. It has been found that the critical night length for the induction of oviparae in two English clones differs by 1.5 h (11 vs 9.5 h, Lees 1973Lees , 1989. In the field, M. viciae would produce oviparae some three weeks earlier than A. pisum.…”
Section: Discussionmentioning
confidence: 99%
“…The proximate cues resulting in wing induction are not fully understood, but include direct contact with other aphids, decreased plant nutritional quality, and exposure to natural enemies (Muller et al 1999;Weisser 2001;Mondor et al 2004Mondor et al , 2005Podjasek et al 2005). Sexual morphs are produced in response to conditions that precede the onset of winter in temperate climates, specifically, increasing dark phase of each day and decreasing temperature (Lees 1989;Via 1992).…”
Section: Introductionmentioning
confidence: 99%